An Epistemological Reflection on Social and Solidarity Economy. Issue 1 (2nd January 2016) - Dash, Anup
Abstract : Social and Solidarity Economy (SSE) is emerging as life affirming solutions to the global crises through the multiple ways people locally reinvent economic life on the margins of the capitalist system based on values of solidarity, reciprocity and sustainability. Although the SSE builds on a strong foundation of real practices and institutions of economic transformation as the way forward for us, this paper argues that this world of practice is in need of its theory to frame discourses and engage with the bigger picture with confidence as an alternative to the dominant economic paradigm. The author argues that the orthodox economics, with its ontological construct of the homo economicus, Cartesian dichotomy and logical positivist epistemology severely constrains our abilities to understand and appreciate economic alternatives based on 'other' rationalities. Hence, there is a need for an epistemological revolution to construct a coherent theoretical framework from the wreckages of the neoclassical economics for the SSE. This paper seeks to outline the basic structure and the key elements of the ontological and the epistemological framework for this 'science-in-the-making' as a step to stimulate further debate for a paradigm revolution.